We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

Hello, can someone help me with this tasks?

1.)

\(\log _2\left(x\right)-\log _4\left(y\right)=0 \)

\(5x^2-y^2=4 \)

2.)

\(64\cdot 9^x-84\cdot 12^x+27\cdot 16^x=0 \)

Guest Jun 18, 2018

edited by
Guest
Jun 18, 2018

#1**+1 **

2)

Solve for x:

64 9^x - 7 12^(x + 1) + 27 16^x = 0

The left hand side factors into a product with two terms:

(16 3^x - 9 4^x) (4 3^x - 3 4^x) = 0

Split into two equations:

16 3^x - 9 4^x = 0 or 4 3^x - 3 4^x = 0

Add 9 4^x to both sides:

16 3^x = 9 4^x or 4 3^x - 3 4^x = 0

9 4^x = 2^(2 x)·3^2:

2^4·3^x = 2^(2 x)·3^2 or 4 3^x - 3 4^x = 0

Equate exponents of 2 and 3 on both sides:

4 = 2 x and x = 2 or 4 3^x - 3 4^x = 0

All equations give x = 2 as the solution:

x = 2 or 4 3^x - 3 4^x = 0

Add 3 4^x to both sides:

x = 2 or 4 3^x = 3 4^x

3 4^x = 2^(2 x)·3^1:

x = 2 or 2^2·3^x = 2^(2 x)·3^1

Equate exponents of 2 and 3 on both sides:

x = 2 or 2 = 2 x and x = 1

All equations give x = 1 as the solution:

**x = 2 or x = 1**

Guest Jun 18, 2018

#2**+1 **

1)

Log_2(x) - Log_4(y) = 0....................(1)

5x^2 - y^2 =4..................................(2)

x = ± sqrt(y^2 + 4)/sqrt(5) sub this into (1) above.

Solve for y:

log(sqrt(y^2 + 4)/sqrt(5))/log(2) - log(y)/log(4) = 0

Bring log(sqrt(y^2 + 4)/sqrt(5))/log(2) - log(y)/log(4) together using the common denominator log(2) log(4):

(log(4) log(sqrt(y^2 + 4)/sqrt(5)) - log(2) log(y))/(log(2) log(4)) = 0

Multiply both sides by log(2) log(4):

log(4) log(sqrt(y^2 + 4)/sqrt(5)) - log(2) log(y) = 0

log(4) log(sqrt(y^2 + 4)/sqrt(5)) - log(2) log(y) = log(y^(-log(2))) + log(5^(-log(2)) (y^2 + 4)^log(2)) = log(5^(-log(2)) y^(-log(2)) (y^2 + 4)^log(2)):

log(5^(-log(2)) y^(-log(2)) (y^2 + 4)^log(2)) = 0

Cancel logarithms by taking exp of both sides:

5^(-log(2)) y^(-log(2)) (y^2 + 4)^log(2) = 1

Multiply both sides by 5^log(2):

y^(-log(2)) (y^2 + 4)^log(2) = 5^log(2)

Factor out the common power log(2) from the left hand side:

((y^2 + 4)/y)^log(2) = 5^log(2)

Raise both sides to the power of 1/log(2):

(y^2 + 4)/y = 5

Multiply both sides by y:

y^2 + 4 = 5 y

Subtract 5 y from both sides:

y^2 - 5 y + 4 = 0

The left hand side factors into a product with two terms:

(y - 4) (y - 1) = 0

Split into two equations:

y - 4 = 0 or y - 1 = 0

Add 4 to both sides:

y = 4 or y - 1 = 0

Add 1 to both sides:

**y = 4 or y = 1 and x =+or- 2 or x=+or- 1**

Guest Jun 18, 2018